Response control performance of a hybrid mass damper applied to a tall building. - Watakabe, Morimasa
A hybrid mass damper system with convertible active and passive modes using a hydraulic actuator (hereinafter referred to as APMD) has been installed to an actual slender tall building with an aspect ratio of eight constructed in Chiba prefecture. In this paper, simulation analysis, force vibration tests and observation of behaviours against moderate wind or some earthquake excitations were carried out to investigate the response control performance of the mass damper system. From the analysis, it was confirmed that on the active mode due to the vibration tests, the damping factors in the 1st mode were about 8-11 percent, satisfactory vibration control effect was obtained and no spillover in the second mode occured. The response values of the peak and the RMS accelerations under the active mode due to the actual wind excitations were reduced to 1/4.5-1/2.0 (average 1/3) in comparison with the responses in non-controlled system. Through the results obtained by these investigations, it was concluded that the mass damper system was quite effective for the response control of the slender tall building to wind loads or earthquakes.
Keywords: Hybrid mass damper; Tall building